Examination of Doping Usage Opinions of Bodybuilding Athletes in the Context of Sports Ethics - Hakan Salim Çağlayan; Ozer Yıldız; Mehmet Kanlı (Türk Spor ve Egzersiz Dergisi)
The aim of this research is to examine the thoughts of bodybuilding athletes on the use of doping from the perspective of sports ethics. Interview method, one of the qualitative research patterns, was used in the research. The research group consisted of 14 elite bodybuilding athletes who participated in international competitions in the bodybuilding branch. In the study, the data were obtained through one-on-one interviews with bodybuilding athletes who volunteered to participate in the research in February 2018 and evaluated by the content analysis method. According to the survey, bodybuilding athletes of Turkey's Youth and Sports Ministry in doping "zero tolerance" policy for their use depending on the doping of athletes of other countries in views on the competitive environment in the contest; Unfair competition, no one who does not use abroad, seeing this branch as a doping sport, getting rid of the backstage, power war of the states, health is more important than success; In their views on the relationship between the diplomatic power of the countries and the use of doping in international competitions, backstage power is important in success, making money negotiations, “Turkish athletes' work is very hard” themes; In his views on the use of doping with the thought that every way should be tried to win at all costs, health is more important than anything, the themes of reaching the desired performance with patience, the truth of this sport, contrary to sports ethics, everything is necessary for victory; knowing that they were not able to detect that they used doping through wipers before an important international competition, felt the necessity to take risks in their country and their own reputation for one-time use of doping; the themes of the athletes they know and observe in their country and other foreign countries using doping, with themes such as a wide variety of health problems and negativity should not be connected to doping in their lives about their physiological and physical changes; It is determined that the athletes they know and observe by using doping bodybuilding in our country and other foreign countries express a wide variety of psychological problems and addiction themes in their opinions about their psychological changes in their lives after the end of the competition life.